(3eSGFd GdNdGas - (3eMeO Hf CMeO Hf eMeO Hf GdLge GdhQGb GdeGdcj GdeQhRj, CHh HcQ,J (B329 (3g` s
(3ChdgG (B:s
(3jHOC CKfGA GdcdGe Yf GdhVhA hChd eG ajg (B: (3hCeG gGgfG GdCYVGA GdCQHYI ai Mce YHGOI hGMOI MJi Cfg dh CaSO GdfjI ai GdCNjQ HWd Gdcd s
(3BNQgG (B:s
(3jfJgi HeSGFd GdcJGHI (B[ (3ef eSGFd GdYJb (B] (3EbJVi SQGjI Edi GdCe SGcdI Zdi GdYJGbI hZjQ eMbbI s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3NRGfI LGeYI GdbQhjjf HaGS (B(489 / 40) s
Keywords: (3Gdabg GdeGdcjs